Consecuencias asociadas al Bullying en los estudiantes del Colegio Mixto 27 de Febrero de la ciudad de Loja periodo septiembre 2015 - julio de 2016. - Torres Sarango, César Augusto (2017)
Bullying, also known as harassment, school bullying, peer abuse for abuse of power or even, is considered an extreme and characteristic form of school violence. It is considered as a social problem that profoundly affects the life project of people, particularly children and young people, having an impact on their development and self-esteem. The general aim of this investigation was directed to determine the consequences associated with the bullying in the students of the Mixed College On February 27 of Loja's city, in included ages from 12 to 15 years. Between the specific aims they are: to establish the existence of bullying in the pupils of the Mixed College On February 27 of Loja's city; to identify the consequences associated with the bullying in the pupils of the above mentioned establishment; to corroborate the type of bullying that exists between the students; and to motivate them to denouncing before the respective authorities, to avoid major consequences. The sample was shaped by 185 pupils and the questionnaire used pre elaborated by the University San Francisco of Quito, which was modified by the author. It is a study of descriptive - transverse type, using several methods to have the summary and systematic presentation of the information, always preserving an idea it adds the consequences that they associate the Bullying. Of the obtained results it was possible to determine that really if it exists bullying or I harass in the pupils understood between the ages of 12 to 15 years of the Mixed College On February 27, in a percentage of 43 % (n=80), and as result of it 20 % (n=37) shows his annoyance before such a situation; on the contrary 11 % (n=20) does not take importance, 7 % (n=13) demonstrates dread or fear and 5 % (n=10) proves to be sad. It is important to mention also that 4 % (n=7), about the polled students has decided about some occasion, not to be present at the educational establishment, for feeling attacked or harassed by his companions, together also it was possible to corroborate that verbal aggression exists with 27 % (n=60) and physical aggression with 8 % (n=24). The bullying can generate dramatic and unsuspected effects in whom they suffer it for what, his study and determination when newly it begins, it is vital for the capture of measures and corrective procedures. Key-Words: bullying consequences, high school, students.